CSR, GCG, Profitability and Firm value: Evidence Form Indonesia’s Energy Sector - Susilawati, Susi; Chasanah, Solichatun; Suryaningsih, Maria; Ramdany (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to analyze the role of social responsibility and good corporate governance in increasing firm value with profitability as an intervening. Design/methodology/approach: The method used in analyzing data is multiple linear regression and intervening variables using the sobel test. The population in this study used energy sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The amount of data used is 90 observation data. Research Findings: The findings in this study indicate that the implementation of corporate social responsibility affects profitability, while good corporate governance has no effect on profitability. The implementation of corporate social responsibility has no effect on firm value, but good corporate governance and profitability affect firm value. Profitability can be an intervening relationship on corporate social responsibility and good corporate governance on firm value. The implementation of corporate social responsibility and good corporate governance is considered very important by companies because it not only has an influence on company profits but is also very important to increase firm value and company sustainability in the future. Theoretical Contribution/Originality: This research contributes to the literature in the implementation of social, environmental and governance activities in energy sector companies without neglecting the company's objectives to earn profits and increase firm value.